Randomized trial of high-dose vitamin D3 supplementation on interleukin-8 modulation in pediatric pneumonia - Setyoningrum, Retno Asih; Kristianto, Wigit; Visuddho, Visuddho; Chafid, Arda Pratama Putra; Hapsari, Rika (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: The immunomodulatory role of vitamin D in respiratory infections has been suggested, but its impact on inflammatory cytokines like interleukin-8 (IL-8) in pediatric pneumonia remains unclear. This study evaluates the impact of vitamin D3 supplementation on serum 25-hydroxyvitamin D3 [25(OH)D3] and IL-8 levels in children diagnosed with pneumonia.Methods: This study was double-blind randomized controlled trial, 45 children with pneumonia were assigned to intervention group (single dose vitamin D3 100,000 IU) (n=23) or placebo group (n=22). Serum 25(OH)D3 and IL-8 levels measured pre- and post-intervention were compared.Results: Vitamin D3 supplementation significantly increased of 25(OH)D3 levels 26.9 (Interquartile Range [IQR] 19.2-31.1) ng/mL to 35.7 (IQR 22.7-48.2) ng/mL (p=0.048). But no significant result was found in placebo group (27.3 [IQR 21.9-33.1] to 24.8 [IQR 21.6-36.2], p=0.884). However, there was no significant difference in IL-8 levels between the supplementation and placebo groups post-intervention (p=0.666).Conclusions: While high-dose vitamin D3 supplementation effectively improved vitamin D levels in children with pneumonia, it did not significantly reduce IL-8 levels. These findings also highlight the importance adequate vitamin D levels but need for further research to explore its role in pediatric pneumonia therapy. (www.actabiomedica.it)